EFFECT OF MAGNESIUM SUPPLEMENTATION ON BLOOD PRESSURE IN GRADE 1 HYPERTENSIVE ADULTS - Boit, Dr. Edwin Kiptolo; Theuri, Dr. Gitahi; Ogweno, Dr. Gordon (Global Journal of Health Sciences, 2020)
Purpose: The primary aim of this study was to assess the change in resting Blood Pressure (BP) following a 6 week magnesium supplementation regimen in grade 1 hypertensive adults. The secondary aim of the study was to assess the change in Resting Heart Rate (RHR) after a 6 week Mg supplementation regimen in grade I hypertensive adults. Methodology: This study employed an experimental research design. In this study, administration of Magnesium (Mg) was controlled by the researcher and the influences on resting BP and RHR observed. A sample of 18 hypertensive adults was used in the study. The significance level was set at p<0.05. Data was determined to be parametric. A paired t-test was used to compare mean differences from baseline, mid-point and post-test within the group Results: There was no significant difference observed at baseline for Systolic Blood Pressure (SBP) and Diastolic Blood Pressure (DBP) within the MGS group (p>0.05). The Magnesium Supplementation Group (MSG) had a SBP and DBP of 143.2 ± 7.0 mmHg and 86.7 ± 4.6 mmHg at baseline. Following supplementation with magnesium (500 mg/day) SBP reduced by -1.1 ±4.8 mmHg and DBP increased by +0.7 ± 6.0 mmHg respectively after 3 weeks and reduced further by -3.4 ± 2.7 mmHg for SBP and -1.0 ± 5.2 mmHg for DBP after 6 weeks. These changes were not statistically significant (p>0.05) after 3 weeks for SBP and DBP respectively, however after 6 weeks they were significant for SBP (p<0.05) but not for DBP (p>0.05). In addition, there was no significant difference observed at baseline for Resting Heart Rate within the MGS group (p>0.05). The MGS group has a RHR of 82.4 ± 11.1 bpm. Following supplementation with magnesium (500 mg/day) RHR bpm reduced by -1.7 ± 6.7 bpm after 3 weeks and reduced further by -2.9 ± 6.1 bpm after 6 weeks. These changes in RHR were not significant (p>0.05) after 3 weeks and 6 weeks. Recommendations for Further Research: For any study dealing with magnesium, intra- erythrocyte magnesium levels need to be taken before and after the study so as to ensure that conclusions drawn from the study are as a direct effect of magnesium